Association Between Care Fragmentation and Total Spending After Durable Left Ventricular Device Implant: A Mediation Analysis of Health Care–Associated Infections Within a National Medicare-Society of Thoracic Surgeons Intermacs Linked Dataset. Issue 9 (6th September 2022) - Kim, K. Dennie; Funk, Russell J.; Hou, Hechuan; Airhart, Austin; Nassar, Khalil; Pagani, Francis D.; Zhang, Min; Chandanabhumma, P. Paul; Aaronson, Keith D.; Chenoweth, Carol E.; Hider, Ahmad; Cabrera, Lourdes; et al.
Abstract : Background: Care fragmentation is associated with higher rates of infection after durable left ventricular assist device (LVAD) implant. Less is known about the relationship between care fragmentation and total spending, and whether this relationship is mediated by infections. Methods: Total payments were captured from admission to 180 days post-discharge. Drawing on network theory, a measure of care fragmentation was developed based on the number of shared patients among providers (ie, anesthesiologists, cardiac surgeons, cardiologists, critical care specialists, nurse practitioners, physician assistants) caring for 4, 987 Medicare beneficiaries undergoing LVAD implantation between July 2009 - April 2017. Care fragmentation was measured using average path length, which describes how efficiently information flows among network members; longer path length indicates greater fragmentation. Terciles based on the level of care fragmentation and multivariable regression were used to analyze the relationship between care fragmentation and LVAD payments and mediation analysis was used to evaluate the role of post-implant infections. Results: The patient cohort was 81% male, 73% white, 11% Intermacs Profile 1 with mean (SD) age of 63.1 years (11.1). The mean (SD) level of care fragmentation in provider networks was 1.7 (0.2) and mean (SD) payment from admission to 180 days post-discharge was $246, 905 ($109, 872). Mean (SD) total payments at the lower, middle, and upper terciles of care fragmentation were $250, 135 ($111, 924), $243, 288 ($109, 376), and $247, 290 ($108, 241), respectively. In mediation analysis, the indirect effect of care fragmentation on total payments, through infections, was positive and statistically significant (β=16032.5, p=0.008). Conclusions: Greater care fragmentation in the delivery of care surrounding durable LVAD implantation is associated with a higher incidence of infections, and consequently, higher payments for Medicare beneficiaries. Interventions to reduce care fragmentation may reduce the incidence of infections and in turn enhance the value of care for patients undergoing durable LVAD implantation.